Adapting quality in homestay hospitality - Kayat, Kalsom (Universiti Utara Malaysia Press, 2007)
Homestay is fast becoming an important tourism product in Malaysia that is speculated to be bring RM300 million in revenue to the economy in 2004.Started basically as a product that offer alternative tourism experience that also act as a strategy to develop communities in the rural areas, by 2005 it had flourished to at least 1,070 homestay units, offering at least 2,140 beds in over 78 villages all over Malaysia.Several, not all, families from each village that establishes itself as a homestay program will participate as homestay hosts that offer accommodation and food in their household for the guests.Other families who are not hosts will usually participate in organizing activities for the guests, especially those who come in groups.Unfortunately, there are concerns that homestay operators lack service orientation.They may not even know their visitors' expectations.To this end, this conceptual paper proposes the adaptation of total quality management concept to strengthen hospitality service offerings of homestay programs in Malaysia.